Hybrid Color Image Compression based DPCM and Slant Transform - mary, Ali Hussien (Nahrain University College of Engineering Journal, 2010)
Nowadays, still images are used everywhere in the digital world. Images take lot of computer space, in many practical situations, all original images cannot be stored, and a compression must be used. Moreover, in many such situations, compression ratio provided by even the best lossless compression is not sufficient, so lossy compression is used. In this paper ,Differential pulse code modulation (DPCM) in slantlet transform and Run Length Code for image compression is used. Apply slantlet transform on each component in the color image(after applying color space conversion from RGB to YCbCr)and encoding Y component by DPCM and encoding Cb and Cr with RLC.The compression ratio and Peak Signal to Noise Ratio (PSNR) are used as measurement tools. When comparing the proposed approach with other compression methods Good result obtained.